Afforestation: Replacing livestock emissions with carbon sequestration. (15th June 2020) - Duffy, Colm; O'Donoghue, Cathal; Ryan, Mary; Styles, David; Spillane, Charles
Abstract: In Ireland, agriculture accounts for 33% of national greenhouse gas (GHG) emissions. Ireland faces significant challenges in terms of emissions reduction and is well off course in terms of meeting binding European Union targets. Flexibility mechanisms will allow Ireland to offset 5.6% of its commitment via sequestration in biomass and soils and land use change. Agricultural emissions in Ireland are largely driven by livestock production. As such, the purpose of this research is to estimate the net GHG emission benefit resulting from a land use change with forest replacing livestock systems (dairy, beef cattle and sheep). We estimate the total carbon sequestration in biomass and harvested wood products, along with the total emissions avoided from each livestock system on a per hectare basis. In addition, the paper compares the social cost of carbon to the average income per hectare of each livestock system. Finally, a hypothetical national planting scenario is modelled using plausible planting rates. Results indicate that the greatest carbon benefit is achieved when forest replaces dairy production. This is due to high emissions per hectare from dairy systems, and greater sequestration potential in higher-yielding forests planted on better quality soils associated with dairy production. The inclusion of harvested wood products in subsequent rotations has the potential to enhance GHG mitigation and offset terrestrial carbon loss. A hypothetical national planting scenario, afforesting 100, 000 ha substituting dairy, beef cattle and sheep livestock systems could abate 13.91 Mt CO2 e after 10 years, and 150.14 Mt CO2 e (unthinned plantations) or 125.89 Mt CO2 e (thinned plantations) over the course of the rotation. These results highlight the critical role for forest land use change in meeting the urgent need to tackle rising agricultural emissions. Highlights: Estimation of carbon storage in forest biomass and harvested wood products on a per hectare basis. Estimation of livestock emissions on a per hectare basis. Generation of a plausible planting scenario, with forest replacing livestock systems. Afforestation replacing livestock offers significant mitigation potential. Replacement of dairy livestock systems offer highest mitigation potential.